2014
DOI: 10.1007/s00039-014-0309-0
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization conjecture and rigidity theory for circle diffeomorphisms with breaks

Abstract: We prove the renormalization conjecture for circle diffeomorphisms with breaks, i.e. that the renormalizations of any two C 2+α -smooth circle diffeomorphisms with a break point, with the same irrational rotation number and the same size of the break, approach each other exponentially fast in the C 2 -topology. As a corollary, we obtain the following rigidity result: for almost all irrational rotation numbers, any two circle diffeomorphisms with a break, with the same rotation number and the same size of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…Rigidity is known to hold for many classes of systems with bounded combinatorics and sufficient smoothness. For example: Kleinian groups [27], circle diffeomorphisms [13,33], critical circle homeomorphisms [6,10,11,31,32], unimodal maps [7, 17-19, 24, 25, 29], circle maps with breakpoints [14,15].…”
Section: Classical Casesmentioning
confidence: 99%
“…Rigidity is known to hold for many classes of systems with bounded combinatorics and sufficient smoothness. For example: Kleinian groups [27], circle diffeomorphisms [13,33], critical circle homeomorphisms [6,10,11,31,32], unimodal maps [7, 17-19, 24, 25, 29], circle maps with breakpoints [14,15].…”
Section: Classical Casesmentioning
confidence: 99%
“…We will refer to (A) as the Denjoy estimate. As we showed in [10], the constant λ ∈ (0, 1) can be chosen uniformly for all T with the same size of the break c and Hölder exponent α.…”
Section: Renormalizations Of Circle Diffeomorphisms With Breaksmentioning
confidence: 99%
“…q n−1 +iqn )| < 1, the bound (3.123) follows by summing up the inequalities In the proof of Theorem 1.2, we will use the following properties of renormalizations of circle diffeomorphisms with a break that were proven in [10]. Let T be a C 2+α -smooth circle diffeomorphisms with a break of size c ∈ R + \{1} at x br = x 0 and an irrational rotation number ρ ∈ (0, 1).…”
Section: Spreading the Estimates To The Whole Circlementioning
confidence: 99%
See 1 more Smart Citation
“…with the same bounded-type combinatorics and zero mean nonlinearities C 1 -smoothly conjugate to each other. In the case of circle maps it was shown that for almost all rotation numbers every two C 2+ε -smooth circle homeomorphisms with a break point, with the same irrational rotation number and the same size of the break are C 1 -smoothly conjugate to each other [7][8][9]. Let us note that statement on the regularity of conjugating map can be obtained by using the convergence of renormalizations of given maps.…”
Section: Introductionmentioning
confidence: 99%